Dos dilemas à esperança : os desafios para a formação e atuação dos professores de Timor-Leste - Silva, Suzi Alves da (2011)
This master's research analyzes the education of Timor-Leste, having as main focus the teachers, seeking to identify the main challenges faced by them for their training and performance and their implications for the educational future of the country. Timor-Leste is a Southeast Asian country that gained independence in 1999; since then it has sought to establish itself as a free and democratic country. Its previous history is marked by domination, having been a Portuguese colony for more than four centuries and later invaded by Indonesia. These different historical periods profoundly marked all instances of the nation, especially education, which has always been a product of the dominant peoples. This research, therefore, brings a historical overview, considering its importance for understanding the developments of the current educational system, especially with regard to teacher training in the face of inherited dilemmas, such as: evasion of teachers, who were mostly from the country invader, poor infrastructure, language limitations, among others. The method used to carry out the research was an approach to ethnography, having a qualitative and quantitative approach. The sources were diversified; I used written, oral and iconographic documents, some already existing and others produced in the research process. Paulo Freire and António Nóvoa are the main theoretical references in this study, in the reflection on teacher training. I could see that the path to autonomy and for there to be a good quality in the educational system in Timor, within a realistic and plausible vision, can be long, there is a lot of work to be done, and this depends on many aspects for it to materialize. . Joint actions by the government, society and international organizations are extremely necessary, especially for the planning of a serious, meaningful and contextualized policy that will serve as the basis for what will become the country's education.(AU)